Physiological and transcriptomic-based analysis reveal the common and specific pathways of clove basil (Ocimum gratissimum) organs in response to cadmium stress - Bin Wang; Yanhui Xiao; Xiao Yuan; Yukun Wang; Dengyue Jiang; Zhaoxia Zhan; Jinming He (Journal of Agriculture and Food Research)
Clove basil has great potentials for effective utilization of cadmium (Cd)-contaminated agricultural soils. However, the molecular basis of clove basil responds to Cd stress on the inter-organ level remains unknown. Here, we investigated the differences of clove basil organs (root, shoot and leaf) in response to Cd stress through comparative transcriptome analyses integrating physiological data. Upon Cd treatment, the roots accumulated the highest levels of Cd, while the leaves contained the least. As a result, Cd treatment significantly reduced the biomass and lowered chlorophyll content in the leaves, suggesting that prolonged exposure to Cd negatively affected the growth of clove basil seedlings. Transcriptomic profiles demonstrated that the responses of different organs to Cd stress were significantly distinct. A total of 2,930, 594, and 2193 differentially expressed genes (DEGs) were identified in the roots, shoots, and leaves, respectively. Functional enrichment analysis revealed significant variations in the unique DEGs among each organ. Notably, the unique DEGs in the leaves were significantly enriched in pathways associated with photosynthesis and signal transduction, whereas the DEGs in the roots were predominantly enriched in pathways associated with the biosynthesis of various secondary metabolites. Furthermore, physiological parameters in different organs in response to Cd stress are also varied, demonstrating coordinated mechanisms across organs to resist Cd stress in clove basil. The overlapping DEGs across organs were more enriched in multiple metabolite biosynthesis pathways. Weighted gene co-expression network analysis (WGCNA) revealed that the DEGs in the brown module were closely associated with Cd content and POD activity, while those in the dark magenta module showed a positive correlation with MDA content and CAT activity. RNA-Seq data was validated through qRT-PCR analysis, which confirmed the reliability of the transcriptomic results. Overall, our study offers valuable insights into the mechanisms by which plants respond to Cd stress across different organs.